Mengurai Fenomena Perdagangan Perempuan di Negara-negara Teluk dan Timur Dekat - Yusnarida Eka Nizmi (Andalas Journal of International Studies (AJIS), 2015)
Women trafficking rises in three ways. First, job vacancy or salary. When someone desperates in economic condition, fake job can be easily success in recruiting a thousand workers by giving fake promise in particular countries. Women trafficking are also running well besause of fake marriage. In some countries which life extremely difficult for unmarried women and marriage is the only way to get convenience , social rights and avoid bullying in her whole life. The second, women trafficking exist because they are sold by their family.Poverty, desperate, and unemployment drive many family sell their children in women trafficking. Finally, love story . Many victims are forced to get involved in women trafficking because of love. These three conditions are the main reason why gulf states and near east become destination for women trafficking. Keywords: human trafficking, women trafficking, cheap labour, gulf states, near east